COMPARISON OF TRANSITION RATES WITH THE LG (0, 1)* SPIRAL-PHASE MODE FIELD DISTRIBUTION IN THE FRAME OF THREE IONIZATION THEORIES - Miladinović, Tatjana B.; Danilović, Nebojša S. (Bulletin of Natural Sciences Research, 2021)
We discussed the tunneling ionization of an Argon atom placed in a strong low-frequency field of Ti: Sapphire laser. The transition rate of the electron obtained with radial polarization LG (0, 1)* spiral-phase mode field distribution included are compared to the basic transition rate. All analyses are given in the frame of the three different ionization theories – Keldysh, PPT, and ADK. We demonstrated that the tunneling transition rate is sensitive to laser polarization and a set field distribution. As well as changes in the azimuthal angle as a parameter on which the given distribution depends.
Keywords: Tunneling ionization; Transition rate; Radially polarized LG (0, 1)* spiral-phase mode